Otimização topológica para obtenção de nova geometria de órtese suro podálica - Furtado, Nathan Meni (Universidade Federal de São Carlos, 2022)
With the improvement in current medicine, many diseases that were once fatal are now manageable with the advances in existing treatments and surgeries, but because of the increased survival, we also have an increase in the number of people who suffer from some physical sequel. To complement the treatment, orthoses are widely used, as they are body external mechanisms that aim to support, relieve or recreate the functioning of an affected limb. The AFO (Ankle-Foot Orthosis) or suropodal orthosis is one of the orthoses currently used for victims of stroke, multiple sclerosis and among other diseases, who suffer deviation sequels related to the ankle and foot. With the increase in stroke survivors in Brazil, the demand for the orthosis, which is provided free of charge by the SUS and which still manually manufactured by physical therapists in the units, has increased. With all this problem, studies to improve the AFO orthosis are large, aiming to solve, for example, the manufacture of more comfortable and optimized models through additive manufacturing, the use of lighter and more resistant materials such as carbon fiber and creation of new optimized and customized designs for the users. All approaches find a major barrier in the complexity of biomechanics, where the efforts of a person's gait are complex and vary with each individual or type of sequel, and the traditional AFO tries to be a middle ground that serves everyone. Therefore, the present work seeks to study one of these areas in order to improve the designs and generate savings for the production of orthotics in the Brazilian health system and serving as support for further research in the area. The chosen area was the simulation of an AFO model through topological optimization, a methodology that uses an algorithm to minimize/maximize the orthosis properties, in order to obtain a new design that is lighter (less volume) and equally resistant. For this, an optimization methodology was applied in the software ABAQUS, which sought to minimize the strain energy of the orthosis while fixing the volume reduction in a percentage (70% of the original volume, for example). In total, three optimizations were simulated with a reduction of 30%, 50% and 70% of the original orthosis volume, and from the results it was possible to arrive at a new proposed design of the AFO with a reduction of 30% of the original volume, which had results of mechanical strain close to the original. The results also validate the usefulness of the proposed methodology through the software ABAQUS, which can serve as a basis for new simulations in AFO orthoses or other orthoses.
Topological optimization to obtain a new geometry of an ankle foot orthosis
Keywords: AFO; Otimização topológica; Órtese; Tecnologia assistiva; Topological optimization; Orthosis; ENGENHARIAS::ENGENHARIA MECANICA::PROJETOS DE MAQUINAS